The Experience of Pediatric Nurses Caring for Tuberculosis Children from Different Ethnic Groups in the New Normal Life: Pediatric nurses - Suza, Dewi Elizadiani; Setiawan; Diah Arruum (Talenta Publisher, 2025)
The cases of Tuberculosis (TB) children in Indonesia increased in 2023 due to the impact of the new normal life. This increase was attributed to delayed immunization, poor nutrition, restrictions on activities, and disruptions to treatment services. The new normal life also affected the increasing number of TB children, in addition to certain ethnic beliefs and culture, causing a significant rise in hospitalized patients and deaths. Therefore, this study aims to explore the experience of pediatric nurses in caring for TB children from various ethnic groups during the new normal life. This study used a phenomenological method, consisting of 12 nurses working in a pediatric ward who were interviewed in an isolated room. The purposive sampling method was used to collect data through semi-structured and in-depth interviews. Data analysis was carried out using the 7-step Colaizzi method. The results showed that a total of 5 themes were identified, namely 1) nurses challenged by patients condition, 2) focus on safety care, 3) the influence of local culture in TB treatment, 4) differences in perceptions of TB between nurses as well as parents, and 5) understanding the perceptions of ethnic beliefs and culture of parents towards the disease. There are still challenges that pediatric nurses must overcome in providing care to patients in hospitals. The results could serve as initial data for developing guidelines or protocols incorporating a cultural competency method, thereby minimizing differences in the provision of nursing care for children with TB.